A RAPID AND SIMPLE ISOLATION OF ENDOTHELIAL-CELL GROWTH SUPPLEMENT FROM MOUSE-BRAIN - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
In-vitro studies using endothelial cells are mainly performed using endothelial cell monolayer cultures (ECC) prepared from umblical cord vein endothelium and grown in tissue culture flasks. These cultures requires growth supplements to promote endothelial cell growth. A specific endothelial cell growth factor (ECGF) was extracted from bovine brain (1,2), gene has been cloned and the nucleotid sequence described (3). Commercially available ECGF for use as endothelial cell culture supplement however, is still produced for convenience from bovine brain. We have developed a simple and rapid method of EC growth supplement production which is considerably cheaper and as effective as the commercially available ECG supplements.
Keywords: ECGF; ENDOTHELIAL CELL; GROWTH SUPPLEMENT; FIBROBLAST